Physician–patient communication at prescription of an additional oral drug for type 2 diabetes and its links to patient outcomes – New findings from the global IntroDia® study. (March 2019) - Edelman, Steven; Belton, Anne; Down, Susan; Alzaid, Aus; Capehorn, Matthew; Gamerman, Victoria; Nagel, Friederike; Lee, Jisoo; Emmerson, James; Polonsky, William H.
Abstract: Aims: To investigate experiences of people with type 2 diabetes (T2DM) at the clinic visit when an additional oral antidiabetes drug (OAD) is prescribed, and how this affects their quality of life, self-management and key outcomes. Methods: We surveyed adults with T2DM from a large multinational study of patient–physician communication during early T2DM treatment (IntroDia®). We examined their experiences when an additional OAD is prescribed ("add-on") after initial OAD monotherapy, focusing on 24 key conversational elements, overall patient-perceived communication quality (PPCQ), and associations with current patient-reported outcomes. The links between PPCQ and people's efforts to delay add-on therapy were also assessed. Results: 4235 people with T2DM prescribed an additional OAD, or a combination of two, were analysed. Exploratory factor analyses of the conversational elements during add-on yielded three coherent, meaningful factors: Encouraging (Cronbach's α = 0.62), Collaborative (α = 0.81), and Discouraging (α = 0.81). PPCQ was positively associated with Encouraging (β = +1.252, p  < 0.001) and Collaborative (β = +1.206, p  < 0.001), but negatively associated with Discouraging (β = −0.895, p  < 0.001). Better PPCQ at add-on was associated with less diabetes distress, greater well-being and better self-care at the present time. Approximately 20% of people bargained (two-thirds successfully) with their physician to delay additional medication. Non-bargaining individuals reported significantly better mean PPCQ, diabetes distress, well-being and self-care than those who bargained. Conclusions: Encouraging and patient-inclusive conversations at add-on moments may improve patient well-being and self-care outcomes. People with T2DM who attempted to delay additional medication reported poorer PPCQ and outcomes.